Antropologi dari St. Gregorius dari Nyssa: Manusia Sebagai Puncak Penciptaan Allah - Ika Santi Pananda; Hendi Wijaya (JURNAL TRANSFORMASI: Jurnal Teologi dan Kepemimpinan, 2025)
This article explores the anthropological thought of St. Gregory of Nyssa regarding humanity as the pinnacle of God's creation. The study employs a qualitative approach with a literature review method, focusing on an analysis of quotations from the works of St. Gregory as well as references to patristic sources such as the writings of St. Maximus the Confessor. The aim is to uncover the early Church's theological understanding of human nature, dignity, and its role in the economy of salvation. The findings indicate that, according to Gregory, humans were created in the image and likeness of God as spiritual, free, and rational beings. The fall did not erase human dignity but positioned humanity as the subject of restoration through the incarnation of Christ. In the salvific work, the incarnation becomes a pivotal moment of restoring human nature toward divine perfection. Ultimately, St. Gregory affirms that universal restoration (apokatastasis) is the fulfillment of God's plan, in which all creation is restored to eternal communion with Him. This study offers significant contributions to the development of Christian anthropology in the context of contemporary education and spirituality